Effect of Pulse Pressure on Vascular Smooth Muscle Cell Migration: The Role of Urokinase and Matrix Metalloproteinase - Redmond, Eileen M.; Cahill, Paul A.; Hirsch, Mindy; Wang, Yi-Ning; Sitzmann, James V.; Okada, Steve S. (Thrombosis and Haemostasis, 1999)
Plasminogen activator (PA) expression plays an important role in smooth muscle cell (SMC) migration and may therefore contribute to mechanical force-induced arterialization of vein grafts. The aim of this study was to determine whether pulse pressure due to pulsatile flow modulates SMC migration via urokinase (u-PA)-dependent mechanisms. Using a perfused transcapillary culture system, human umbilical vein SMC were exposed to pulse pressures (0-56 mmHg), in the absence or presence of human umbilical vein endothelial cells (EC) by varying pulsatile flow rates (0 ml/min to 25 ml/min). SMC cultured in the absence of EC increased their migration following exposure to increased pulse pressure (248 ± 14%). Both u-PA and matrix metalloproteinase 1 (MMP-1) expression was significantly elevated in SMC exposed to pressure as compared to static controls. The role of proteases in the pulse pressure-induced enhancement of SMC migration was confirmed following pretreatment with aprotinin, an anti u-PA antibody and metalloproteinase inhibitors (181 ± 14% for aprotinin vs. 256 ± 25% for control, 108 ± 4% for anti-u-PA antibody vs. 233 ± 17% for non-immune IgG, and 114 ± 9% for BB-94, 105 ± 7% for BB-3103 vs. 222 ± 5% for control). Using SMC derived from u-PA gene knockout mice, the SMC migratory response to increased pulse pressure was completely inhibited despite a significant increase in MMP expression in these cells. These results suggest that pulse pressure due to pulsatile flow induces SMC migration in vitro via u-PA and MMP-dependent mechanisms. Moreover, u-PA gene deletion results in blunting of pressure-induced SMC migration despite the endogenous upregulation of metalloproteinase. Modulation of u-PA expression by pressure may thus represent an important mechanism whereby hemodynamic forces regulate smooth muscle cell migration.